Estudo e comparação da eficiência da ação coagulante do polímero natural tanino e do cloreto férrico no tratamento de efluente têxtil - Moreira, Isabela (2016)
Textile industry consumes large amounts of water and chemicals in its production processes. In consequence of that, this type of industry is a big generator of wastewater with high color and turbidity and rich in organic matter and recalcitrant substances. To minimize environmental problems associated with inadequate emission of textile wastewater in water bodies, many processes has been used to treat this sort of effluent. Because of its easy application and low cost, one of the most popular processes applied in textile wastewater primary treatment is coagulation-flocculation followed by sedimentation. Considering these facts, this paper aimed to compare the removal efficiency of apparent color, total solids and turbidity using ferric chloride, a natural tannin-based coagulant (Tanfloc SG) and the combination of both ferric chloride and Tanfloc SG in the treatment of a textile wastewater by coagulation-flocculation-sedimentation process. The raw textile wastewater was collected in the equalization tank outlet of a Textile Industry´s Treatment Plant located on northern Paraná. Central Composite Rotatable Design (CCRD) was used as experimental design. Coagulant concentration and settling time were considered as factors and removal efficiencies of color, turbidity and total solids were considered as dependent variables. Tests were run in the Jar Test apparatus. The coagulant concentration ranged from 300 to 800 mgL-1 and sedimentation time varied from 0 to 40 minutes. For tests using Tanfloc SG and the combination of ferric chloride and Tanfloc SG, it was applied rapid mixing of 90 rpm during 2 minutes and slow mixing of 35 rpm during 20 minutes. For tests using only ferric chloride, it was used rapid mixing of 150 rpm for 5 minutes and slow mixing of 30 rpm for 15 minutes. The coagulant Tanfloc SG did not show good results for removal efficiencies of the evaluated parameters. The test ran with 800 mgL-1 of ferric chloride and 20 minutes of sedimentation achieved the best results for removal efficiency of total solids (13.2%), apparent color (25%) and turbidity (47.6%), but reduced the pH to 4.29. Statistical Models, however, indicated that treatment using the combination of ferric chloride and Tanfloc SG could achieve the highest removal efficiencies of apparent color (21.9%) and turbidity (40.7%). Moreover, tests ran with combination of coagulants showed smaller drop in pH. Low removal efficiencies values could be caused by excess of organic matter in raw wastewater, which can make it harder for coagulation and flocculation to occur. Within the boundaries of this study, coagulation and flocculation using combination of ferric chloride and Tanfloc SG seems to be the most suitable alternative for primary treatment of textile wastewater.